Bank runs without sequential service - David Andolfatto; Ed Nosal (Federal Reserve Bank of Atlanta, 2018)
Banking models in the tradition of Diamond and Dybvig (1983) rely on sequential service to explain belief-driven runs. But the run-like phenomena witnessed during the financial crisis of 2007-08 occurred in the wholesale shadow banking sector where sequential service is largely absent, suggesting that something other than sequential service is needed to help explain runs. We show that in the absence of sequential service runs can easily occur whenever bank-funded investments are subject to increasing returns to scale consistent with available evidence. Our framework is used to understand and evaluate recent banking and money market regulations.
Keywords: G01; G21; G28; 330; bank runs; increasing returns to scale; mechanism design